Nutrient composition of swiftlets (aerodramus fuciphagus) guano from the east coast economic region (ECER) of Malaysia and its potential as an organic fertilizer. - Azizon Abdullah (2017)
The edible-birdnest (EBN) industry in Malaysia is highly regarded as a high-value economic sector and appears as a new strategic economic initiative by the Malaysian government. However, there is a growing concern over the quality of EBN particularly those produced by the swiftlet ranchers. Accumulation of swiftlet guano in the birdhouses over time has led to deteriorating quality of EBN and environmental problems such as the nitrate and nitrite issues. Removing the guano from the birdhouses requires proper waste management which further allows us to exploit the hidden values of the guano. The study therefore attempted to investigate the value-added features of swiftlet guano as an alternative organic fertilizer for agricultural purpose. A total of 114 samples of swiftlet guano were collected from 19 districts in the ECER region covering the state of Kelantan (n:55, 8 districts), Terengganu (n:49, 2 districts) and Pahang (n:10, 9 districts). These samples were collected from accredited SALT (Skim Akreditasi Ladang Ternakan) birdhouses, which were certified establishments from the DVS authorities. Samples were analysed for Proximate and selected microbiological analyses. Swiftlet guano samples collected from the birdhouses in Pahang had the highest dry matter (DM, 85.27% + 4.61%), organic matter (OM, 77.56% + 4.51%), nitrogen (N, 15.76% + 0.20%), ether extract (EE, 1.97% + 1.22%) and nitrates (NO3, 69.75% + 0.89%). Ash, (Ash, 7.71 + 1.74%), Calcium (Ca) and phosphorus (P) were highest in guano from Kelantan with the values of 1.13% + 0.36%, 1.21% + 0.20% respectively. Guano from Terengganu had the highest potassium (K, 1.17% + 0.03%) as compared to the overall mean of 1.14% + 0.10% from the three states.